Perancangan Sistem Informasi Pemesanan Ruang Rapat Dan Konsumsi Di Bagian Umum Sub. Rumah Tangga Universitas Sebelas Maret Surakarta - tasmin - tasmin; Chairullah - Naury; Kresno Ario Tri Wibowo (Indonesian Journal of Information Technology and Computing (IMAGING), 2022)
The process of borrowing meeting rooms currently running in the General Section of the Sub-Household of Sebelas Maret University Surakarta (UNS) is done manually. The meeting committee met with the General Section of the UNS Sub-Household to order a meeting room and its consumption. Then the Admin of the General Section of the UNS Sub-Household saw the record data in the room reservation book in advance to inform which room could be used for meetings. To speed up and simplify the process of borrowing a meeting room, it is necessary to design a meeting room reservation information system. Based on the description of the background, it can be formulated that the problem to be solved in this research is "How to design an information system for ordering meeting rooms and consumption in the General Section of the UNS Sub-Household". Limitation of the problem that the author discusses in the research focused on designing an information system for ordering space and consumption in the General Section of the UNS Sub-Household. The method used to design an information system for meeting room reservations and consumption using the System Development Life Cycle (SDLC) with the Waterfall model. The programming language used to design this system is PHP Native and MySQL database as data storage media. With the design of the meeting room reservation information system, it is hoped that it will facilitate and speed up the process of ordering meeting rooms in the General Section of the UNS Sub-Household.Â Â Â